Contested Markets: An overview (Antropolítica - Revista Contemporânea de Antropologia, 2017)
This article provides an overview of the sub-area of new economic sociology, (NES), known as “contested markets”. The involvement of both interests and values in the confection of markets has always been a leitmotif of economic sociology and many authors have dealt with the different ways in which markets have been challenged. The very organization of markets involves exclusions which at any time may provide the basis for contestations. Nevertheless, demographic trends, the rapid advance of the scientific and technological frontier, and the privatization of what were previously considered key public goods, have led to a more fundamental questioning of the acceptability of extending markets into new areas of social and private life. We review the different contributions of NES to this theme and, in particular, examine the major contribution provided by Philippe Steiner and colleagues to an understanding of the mechanisms put in place to deal with contestation in the construction of markets. A related, important, contribution on the dynamic of illegal markets by Beckert and Wehinger and the degree to which these can be included within the framework of market analysis, is also discussed. The article concludes with a discussion of Steiner´s original contribution on the “don” to an understanding the hybridization of reciprocity and exchange in the emergence of contested markets.